THE THEORY OF LINGUISTIC RELATIVITY AND ITS REFLECTION IN TED CHIANG’S “STORY OF YOUR LIFE” (Scientific journal of the Fergana State University, 2025)
This article explores the application of the theory of linguistic relativity in Ted Chiang's science fiction story "Story of Your Life" (1998). The core principles of the Sapir-Whorf hypothesis and their interpretation in a literary context are examined. The analysis focuses on how the language of aliens influences the protagonist's perception of time and consciousness, reflecting ideas about the interrelation between language and thought. The research is based on recent studies in linguistics, philosophy of language, and literary criticism. The author emphasizes the significance of science fiction in addressing complex linguistic and philosophical concepts.